Diseño de una línea de producción para la elaboración y envasado de licor de carambola en la ciudad de Quevedo - Carmigniani Molina., Kenia Rosselin (2021)
This is a qualitative research, it was conducted with a sample of 424 people in the city of Quevedo, it was concluded that most people have consumed some alcoholic beverage on a monthly basis; the quality, taste and price are the main factors that influence the purchase of a carambola-based liquor, the bottle presentation is glass with a content of 600 milliliters transparent color. It was determined that the preferred places for consumption are at home or at the home of someone with whom they have a work or personal relationship. It is necessary to have 3 operators for the optimal operation of the production line. The production line will be implemented in the city of Quevedo because it meets the requirements for its work with a production area of 70 m² with a production process consisting of weighing, selection and washing, pressing, filtering, fermentation, distillation, resting or maturation, filtering, and packaging. The initial investment for the project is $ 30,000.00 will be financed by a bank; the selling price was determined at $3.48, and the annual production will be 42,408 bottles of 600 ml. The annual net income was determined to be $147,579.84. The NPV was determined to be $148,657.53 with a benefit cost of 2.30 and an IRR of 21.99%. The project is feasible since the NPV and Benefit Cost are greater than one and the IRR is greater than the opportunity cost of money. The capital will be recovered in approximately 3 years. Key words: Liquor, Design, Process, Production.